L'industria culturale e creativa Giovani e innovazione in Campania - Savonardo, Lello (Culture giovanili, 2022)
Cultural and creative industries play an important role in the processes of cultural, social and economic development of Italy. In particular, in South Italy, Campania region is characterized by a considerable creative effervescence, which represents a strategic resource for the growth of the territory and the empowerment of young people. However, in this territorial context, characterized by profound internal differences in the availability of resources and services, the "creativity-culture-development" axis constitutes a critical issue, highlighted by the social, economic and organizational repercussions of the Covid-19 pandemic. Starting from a theoretical reflection on the cultural and creative industry, the book presents the results of an exploratory study conducted between 2020 and 2021 by the Osservatorio Territoriale Giovani (OTG) of the Department of Social Sciences of the University of Naples Federico II in collaboration with the Campanian local government. The research is based on twenty qualitative interviews to privileged witnesses and returns a map of the limits and resources of the Campanian cultural and creative industries in relation to the impact of the pandemic and provides some ideas for the future institutional initiatives aimed at strengthening the sector and promoting youth creativity.